Control Freedom Index of Integrated Energy System and Its Impact on Economic Dispatch - Tao ZHENG; Zemei DAI; Jiahao YAO; Jing CAO; Shuomin WU; Kaifeng ZHANG (Zhongguo dianli)
Integrated energy system (IES) provides users with diversified energy supply services through the coupling conversion of multiple energy flows. Compared with conventional independent energy supply systems, the IES has greater degree of control freedom. In order to measure the degree of control freedom, this paper firstly proposes a convertibility index to characterize the mutual conversion ability of multiple energy flows, and a substitutability index to represents selection opportunities for alternative energy at the user side. In addition, the calculation methods for the convertibility index and the substitutability index are provided. Secondly, considering the influence of control freedom on the optimal operation of the IES, an economic dispatch model of the cooling-heating-power-gas IES is established. Finally, a case simulation is carried out, and the results shows that improving the two control freedom indexes of the convertibility and substitutability of the integrated energy system can reduce the economic dispatch cost of the system.